27-Hydroxycholesterol contributes to disruptive effects on learning and memory by modulating cholesterol metabolism in the rat brain. (6th August 2015) - Zhang, D.-D.; Yu, H.-L.; Ma, W.-W.; Liu, Q.-R.; Han, J.; Wang, H.; Xiao, R.
Highlights: 27-OHC is a critical mediator of the detrimental effects on spatial learning memory in rats. 27-OHC significantly increased the content of cholesterol in brain tissues. 27-OHC significantly decreased in HMG-CR and LDLR expressions. 27-OHC significantly increased in mRNA expressions of CYP46A1 and LXR-β. 27-OHC significantly up-regulated expressions of LXR-α and ABCA1. Abstract: Cholesterol metabolism is important for neuronal function in the central nervous system (CNS). The oxysterol 27-hydroxycholesterol (27-OHC) is a cholesterol metabolite that crosses the blood–brain barrier (BBB) and may be a useful substitutive marker for neurodegenerative diseases. However, the effects of 27-OHC on learning and memory and the underlying mechanisms are unclear. To determine this mechanism, we investigated learning and memory and cholesterol metabolism in rat brain following the injection of various doses of 27-OHC into the caudal vein. We found that 27-OHC increased cholesterol levels and upregulated the expression of liver X receptor-α (LXR-α) and adenosine triphosphate (ATP)-binding cassette transporter protein family member A1 (ABCA1). In addition, 27-OHC decreased the expression of 3-hydroxy-3-methylglutaryl-CoA reductase (HMG-CR) and low-density lipoprotein receptor (LDLR) in rat brain tissues. These findings suggest that 27-OHC may negatively modulate cognitive effects and cholesterol metabolism in the brain.